Predictors of Cyberbystander Intervention Among Adolescents - Aliberti, Maria (Journal of interpersonal violence, 2023)
The purpose of the current study was to examine the association between personal characteristics and the steps of the bystander intervention model (i.e., notice, interpret as emergency, accept responsibility, know how to intervene, and act) applied to cyberbullying. Examining bystander intervention as discrete steps instead of the single act has advantages for training individuals to intervene when they observe these acts of interpersonal violence. The five-step bystander intervention model has been applied to examine bystander intervention in traditional bullying, sexual assault, and drinking behavior, but not cyberbullying. In this study, we examine how specific personal characteristics (social support, social-emotional wellness, cognitive empathy, and affective empathy) are related to each step of the model. Data on students’ perceptions of these characteristics and their engagement in the five-step model were collected from 872 sixth-grade through twelfth-grade students ages 11 to 18 in the southeastern area of the United States. Using multi-group path analysis, associations between the characteristics and steps were examined for boys and girls separately. Results indicated that social support was significantly associated with step 2 (interpreting as an emergency), step 4 (know how to intervene), and step 5 (acting). Affective empathy was significantly associated with the first four steps of the model. Social-emotional wellness was only significantly associated with step 1 and cognitive empathy was not significantly associated with any of the steps. These results suggest that it may be important to emphasize positive relationships, affective empathy, and social support for interventions primarily directed at reducing cyberbullying. Training adolescents to intervene in cyberbullying and also to increase these characteristics is important to consider.